Comparison of four nasal sampling methods for the detection of viral pathogens by RT-PCR-A GA(2)LEN project - Spyridaki, I. S.; Christodoulou, I.; de Beer, L.; Hovland, V.; Kurowski, M.; Olszewska-Ziaber, A.; Carlsen, K. H.; Lødrup-Carlsen, K.; van Drunen, C. M.; Kowalski, M. L.; Molenkamp, R.; Papadopoulos, N. G. (J Virol Methods, 2009)
The aim of this study was to compare the efficacy and patient discomfort between four techniques for obtaining nasal secretions. Nasal secretions from 58 patients with symptoms of a common cold, from three clinical centers (Amsterdam, Lodz, Oslo), were obtained by four different methods: swab, aspirate, brush, and wash. In each patient all four sampling procedures were performed and patient discomfort was evaluated by a visual discomfort scale (scale 1-5) after each procedure. Single pathogen RT-PCRs for Rhinovirus (RV), Influenza virus and Adenovirus, and multiplex real-time PCR for RV, Enterovirus, Influenza virus, Adenovirus, Respiratory Syncytial Virus (RSV), Parainfluenza virus, Coronavirus, Metapneumovirus, Bocavirus and Parechovirus were performed in all samples. A specific viral cause of respiratory tract infection was determined in 48 patients (83%). In these, the detection rate for any virus was 88% (wash), 79% (aspirate), 77% (swab) and 74% (brush). The degree of discomfort reported was 2.54 for swabs, 2.63 for washes, 2.68 for aspirates and 3.61 for brushings. Nasal washes yielded the highest rate of viral detection without excessive patient discomfort. In contrast, nasal brushes produced the lowest detection rates and demonstrated the highest level of discomfort.
Keywords: 80 and over Child Female Humans Male Middle Aged Nasal Cavity Prospective Studies RNA Viruses RNA; Adolescent Adult Aged Aged; Viral Respiratory Tract Infections Reverse Transcriptase Polymerase Chain Reaction Young Adult